Academic libraries as hubs of artificial intelligence competency - Nuno Miguel Teixeira Sousa (Discover Artificial Intelligence)
Abstract At a time when algorithmic automation is quietly reshaping the ways in which knowledge is produced, accessed and legitimized, academic libraries face an urgent imperative: to move from being mere information intermediaries to becoming critical mediators of artificial intelligence (AI) literacy. This article proposes a disruptive and post-digital reading of academic libraries as epistemic infrastructures that resist algorithmic hegemony and promote cognitive justice. Articulating contributions from critical librarianship, AI literacy theory and philosophy of information, a conceptual model is outlined with six dimensions that position libraries as central agents in the formation of informed, critical citizenship that resists the opacity of digital platforms. The article concludes by defending a new post-digital librarian ethos: less focused on technical neutrality and more committed to the creation of plural, open and democratically distributed cognitive futures.